Design, characterization and antimalarial efficacy of PEGylated galactosylated nano lipid carriers of primaquine phosphate. (17th November 2018) - Baruah, Uday Krishna; Gowthamarajan, Kuppusamy; Ravisankar, Vanka; Karri, Veera Venkata Satyanarayana Reddy; Simhadri, Praveen Kumar; Singh, Vineeta; Babu, Phanithi Prakash
Abstract: This study was aimed to design and optimize primaquine phosphate (PQ) loaded nanostructured lipid carriers (NLCs) using response surface methodology. The optimized NLCs were evaluated for various physical and morphological characterizations. The in vitro studies for drug release showed that PQ loaded NLCs had a sustained release up to 72 h and the stability studies confirmed that the PQ-NLCs were stable for 90 d at 4 °C and 25 °C. In vitro erythrocyte toxicity revealed that PQ-NLCs were less toxic than the pure drug. In vitro parasite growth inhibition assay showed an IC50 value of 71.11 ± 6.47 ng/ml for the 3D7 Plasmodium falciparum (CQ sensitive) strain and 263.86 ± 5.68 ng/ml for RKL9 P. falciparum (CQ resistant) strain for the PQ-NLCs. Enhanced parasitaemia suppression of 99.46% at 2 mg/kg/d, a better suppression of parasitaemia of about 28% more than pure drug and a higher survivality rate of 66.66% even after the 35th day was observed for the PQ loaded NLCs. Also from the comparative fluorescent imaging study, it was clearly observed that accumulation of PQ-NLCs in the liver was more that of the pure drug. These results clearly indicated that the limitations of antimalarial drug PQ can be overcomed by loading it into the NLCs.